A multi-source combined operation low carbon economy dispatch considering flexible participation of nuclear power in peaking - WU Xi; CHEN Kangwen; GUO Qisheng; LIU Yichen; YUE Fuchang (电力工程技术)
In the coastal power grid with a high proportion of nuclear power units and new energy power generation equipment, the pressure of peak regulation on system is severe. In order to achieve the demand of system peak regulation and fully explore the capacity of nuclear power peak regulation, the optimized dispatch model of nuclear-photovoltaic-electrochemical energy storage-pumped storage-thermal multi-source combined operation with flexible output of nuclear power to participate in peak regulation is established. Firstly, 0-1 variables are used to accurately linearize the flexible address to nonlinear output of nuclear power. Secondly, complete system operation constraints is established, considering the operating characteristics and cost composition of each power unit. Finally, based on traditional economic optimization goal, different carbon trading mechanisms are introduced, considering the system′s new energy level. The simulation example verifies the effectiveness of the proposed model. The results show that the proposed scheduling model effectively alleviates the system′s peak pressure and reduces the frequent start-stop of thermal power units by the flexible output of nuclear power, thus improving the consumption level of new energy. The system operation is economical and low-carbon.